NILAI-NILAI PENDIDIKAN AKHLAK DALAM PERSPEKTIF KITAB TA’LIM MUTA’ALLIM KARYA IMAM AZ-ZARNUJI - Armaya, Jeyssika; Meilinda, Poppy; Musthofa, Muhammad Iqbal; Ernaz, Ainul Umami; Wiguna, Satria (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2023)
This study aims to explore in depth the concept of moral education in Ta'lim Muta'allim by Imam Az-Zarnuji, which is still used in many Islamic boarding schools as a guideline for character building. Moral education is considered very important in shaping individuals who are not only intellectually intelligent but also wise in their attitudes and behavior. The method used in this study is a literature review, involving a direct analysis of the text of Ta’lim Muta’allim in both Arabic and its translation, supported by other books and journals discussing the thoughts of Imam Az-Zarnuji. The results of the study show that Imam Az-Zarnuji emphasizes the importance of sincere intentions in seeking knowledge, respect for teachers, patience in learning, and avoiding futile actions. He also teaches the importance of forming good habits, choosing righteous friends, and managing time. The methods he used are very touching and easy to apply, such as giving clear advice, telling stories of scholars, and fostering awareness of the importance of one's relationship with Allah. This book not only teaches ethics in learning but also in daily life. By understanding and applying the ethical values of Ta’lim Muta’allim, it is hoped that a generation will emerge that is not only intelligent but also civilized, humble, and responsible. This research underscores the importance of reviving ethical values in modern education as the foundation for the formation of noble character. Penelitian ini bertujuan untuk menggali secara mendalam konsep pendidikan akhlak dalam Ta’lim Muta’allim karya Imam Az-Zarnuji yang hingga kini masih digunakan di banyak pesantren sebagai pedoman pembentukan karakter pelajar. Pendidikan akhlak dinilai sangat penting dalam membentuk manusia yang tidak hanya cerdas secara intelektual tetapi juga bijak dalam bersikap dan bertingkah laku. Metode yang digunakan dalam penelitian ini adalah studi pustaka, dengan mengkaji langsung teks kitab Ta’lim Muta’allim baik dalam bahasa Arab maupun terjemahannya serta didukung oleh buku dan jurnal lain yang membahas pemikiran Imam Az-Zarnuji. Hasil penelitian menunjukkan bahwa Imam Az-Zarnuji menekankan pentingnya niat yang tulus dalam menuntut ilmu, penghormatan kepada guru, kesabaran dalam belajar serta menjauhi perbuatan sia-sia. Beliau juga mengajarkan pentingnya membentuk kebiasaan baik, memilih teman yang saleh serta menjaga waktu. Metode yang beliau gunakan sangat menyentuh dan mudah diterapkan, seperti memberi nasihat yang jelas, menceritakan kisah-kisah ulama dan membangun kesadaran akan pentingnya hubungan dengan Allah. Kitab ini bukan hanya mengajarkan akhlak dalam belajar tetapi juga dalam kehidupan sehari-hari. Dengan memahami dan menerapkan nilai-nilai pendidikan akhlak dari Ta’lim Muta’allim, diharapkan lahir generasi yang tidak hanya cerdas tetapi juga beradab, rendah hati dan bertanggung jawab. Penelitian ini menggarisbawahi pentingnya menghidupkan kembali nilai-nilai akhlak dalam pendidikan modern sebagai dasar pembentukan karakter mulia.